RESPON PERTUMBUHAN SERTA PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DAN CABAI RAWIT (Capsicum frustescens L.) TERHADAP APLIKASI PUPUK SOLID DAN POC HAYATI PADA POLA TANAM TUMPANG SARI - Muhammad Maulana Siregar; Selvia Sutriana (DINAMIKA PERTANIAN, 2025)
This study aims to determine the interactions and main applications of solid and biological POC fertilizers on the growth and production of shallots and cayenne pepper in an intercropping system. This study used a 2-factorial Completely Randomized Design (CRD). The first factor is solid fertilizer, with 4 levels: 0, 500, 1000, and 1500 g/plot, while the second factor is biological POC, with 4 levels: 0, 2, 4, and 6 ml/L water. There were additional 2 units of experiments for the monoculture planting of shallots and cayenne pepper. The results showed that the interaction between solid and biological POC was not significant for shallot parameters. Still, the main effect of solidity was significant on height, number of tubers, wet weight per clump, and dry weight per clump, with the best dose of 1500 g/plot, while the main effect of biological POC was significant on wet weight per clump and dry weight per clump, with the best concentration of 4 ml/L water. The interaction of solid and biological POC was significant on the height of cayenne pepper, with the best treatment of 1500 g/plot and 4 ml/L of water, while the main effect of solid was significant on height, flowering age, productive branches, and residual fruit, with the best dose of 1500 g/plot, but the main effect of biological POC was not significant for cayenne pepper. The best land-to-water ratio was 3.78 with no solid treatment and 2 ml/L POC water.